EFFECT OF THE SCALE FORMATION ON THE PERFORMANCE OF RECIRCULATION MSF PLANT - JASSIM, ALA'A ABDULRAZAQ (Basrah Journal for Engineering Sciences, 2014)
The effect of fouling due to scale formation of pre-heater tubes on the thermal performance of Reticulating multi stage flash Distillation plant performance ratio and the increase of the ratio of Makeup water to the product Quantity for a 5MGPD recirculating System has been prediction The results appeared That eth Effect of scale formation is more Effected as the Maximum brine temperature decrease.